Selangkah ke ” All Star’ DM54 (Go Glow)” UiTM Cawangan Perak / Al-Amin Abdul Razi - Abdul Razi, Al-Amin (Universiti Teknologi MARA, Perak, 2023)
26 August 2022 : UiTM Perak Administration Off ice has organized a briefing session named “ Selangkah Ke‘All Star DM54 (Go Glow) ” virtually through the Webex application. The briefing session was held toexplain the procedure and process for the promotion of Senior Lecturers DM51 and DM52 to AssociateProfessor grade DM54. In addition, there was also questions and answers session.